Criteria for Protectability of a Creative Product: Creative Nature and Originality - SOLOMONENKO, Liliya Alexandrovna; DULTSEV, Anton Igorevich (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
A creative product as a copyright object must be appropriately protected. However, according to the legal systems of different countries, the availability of an objective form of expression is not enough to recognize the result of intellectual activity as a copyright object. The international law does not provide an exhaustive list of criteria for a creative product to get copyright protection, and the set of currently existing approaches are so different that the authors appear on unequal terms. Thus, programs and software, as copyright objects, in some cases have become so vulnerable that their creators prefer to apply patent-legal protection. The point of dispute is the lack of standardized specifications for protectability of the creative products of literature, science, art, even within the same legal family. Despite the fact that the national doctrines contain the terms ‘originality’ and ‘creative nature’, their use is usually based on synonymousness and interchangeability, that leads to the distortion of the essence of the analyzed object – a creative product. Thus, a more precise definition of the criteria is required, which are aimed at providing a creative product with adequate protection and using mechanisms for the protection of exclusive rights. It is necessary to differentiate the criteria in order to determine the protectability of creative products, have the possibility to eliminate or bridge the disputes between the authors and rights holders, as well as to consider more objectively the lawsuits related to the nature of the object of legal relations. The aim of the article is not to analyze the legal solutions in the field of legal terminology, but to study the nature of definitions in the legal apparatus of different countries.